Teacher’s Perception of Web-Based Educational Games for Slow Learner Students: A Qualitative Case Study - Ambarsari, Melani; Winarno, Winarno; Adi, Fadhil Purnama (Social, Humanities, and Educational Studies (SHES): Conference Series, 2026)
The rapid development of digital technology has encouraged the integration of innovative learning media in elementary education, including web-based educational games. However, their implementation for slow learner students requires careful pedagogical consideration, particularly from teacher’s perspectives. This study aims to explore teacher’s perceptions of using web-based educational games to support slow learner students in elementary schools. Employing a qualitative case study approach, the research involved a fourth-grade teacher and four slow learner students at Panularan Elementary School, Surakarta, Indonesia. Data collection comprised classroom observations, semi-structured interviews, open-ended questionnaires, and document analysis. The findings reveal that the teacher perceived web-based educational games as beneficial for enhancing student engagement, supporting structured repetitive learning, and facilitating cognitive responses among slow learners. Visual elements, immediate feedback, and step-by-step tasks emerged as key supportive features. Despite challenges like limited instructional time and technological resources, teachers maintain positive attitudes toward continued implementation. Positive teacher perceptions prove crucial for successful game integration, advancing inclusive adaptive learning practices. Ultimately, this study underscores that the teacher’s pedagogical agency and belief system act as the primary catalysts for transforming digital tools into effective cognitive scaffolds for diverse learners in regular classrooms.